Estudo da condutividade protônica do eletrólito sólido de cerato de bário dopado para uso em células a combustível de óxido sólido - (:unkn) unknown (Universidade Federal de Goiás, 2018)
The proton conductors have wide applications, such as in solid oxide fuel cells, hydrogen separation membranes, hydrogen bombs, among others. These technologies are intended to generating clean and sustainable energy. Among the materials with this property is the BaCeO3 barium cerate, which presents low thermal activation energy for proton conductivity in intermediate working temperature. However, due to its highly basic character, when in operation in atmospheres with acid gases, such as CO2, SO2 and H2O this presents a certain chemical instability. It is known in the literature that doping of BaCeO3 improves this instability. In this work, pure BCO and yttrium doped cerium (BaCe1-xYxO3- δ / BCYO) was synthesized by the polymer precursor method. The powders obtained in the syntheses will be characterized by XRD and a mean crystallite size of 23 nm was obtained which indicates the nanometric particle size. The pellets conformed and sintered at 1600 ºC with a 4-hour plateau at a rate of 5 °C / min were then subjected to impedance spectroscopy tests and showed where it was verified that doping with the 15% yttrium content presented the best result with similar conductivity and activation energy lower than the pure sample.
Study of the proton conductivity of solid barium cerate doped electrolyte for use in solid oxide fuel cells
Keywords: Cerato de bário; Eletrólito sólido; Células a combustível; Condutividade protônica; Espectroscopia de impedância; Barium cerate; Solide electrolyte; Fuel cells; Próton conductivity; Impedance spectroscopy; CIENCIAS EXATAS E DA TERRA::QUIMICA